2004
DOI: 10.2975/28.2004.177.180
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Family Treatment for Parents with Severe Psychiatric Disabilities.

Abstract: This paper reports a case series of families participating in Integrated Family Treatment, a home-based parent training and family support program for parents with severe psychiatric disabilities. All 8 families who entered the program over 6 months were followed for 1 year. Seven families remained in treatment for more than 10 months and rated the program highly. Six of the seven parents (85.7%) remaining in treatment improved on one or more measure of parent skills. Integrated Family Treatment is a promising… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…These included the children of a parent/s who had mental illness (Grant et al ., 2008; Grove et al ., 2015a; Noether et al ., 2007), children of a parent/s with problematic substance use (Templeton and Sipler, 2012), and grown up children whose parent/s had a mental illness (Knutsson‐Medin et al ., 2007; Nilsson et al ., 2015). Most seemed to be provided in service or clinical settings, including residential (Killeen and Brady, 2000; McComish et al ., 2003) and inpatient care (Isobel et al ., 2015; O'Brien et al ., 2011), but some were specifically provided in the family's home setting (Brunette et al ., 2004; Gewirtz et al ., 2009; Gruber et al ., 2001; Maybery et al ., 2015; van Doesum et al ., 2008) and two were provided via DVD and/or the internet (Grove et al ., 2015b; van der Zanden et al ., 2010).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These included the children of a parent/s who had mental illness (Grant et al ., 2008; Grove et al ., 2015a; Noether et al ., 2007), children of a parent/s with problematic substance use (Templeton and Sipler, 2012), and grown up children whose parent/s had a mental illness (Knutsson‐Medin et al ., 2007; Nilsson et al ., 2015). Most seemed to be provided in service or clinical settings, including residential (Killeen and Brady, 2000; McComish et al ., 2003) and inpatient care (Isobel et al ., 2015; O'Brien et al ., 2011), but some were specifically provided in the family's home setting (Brunette et al ., 2004; Gewirtz et al ., 2009; Gruber et al ., 2001; Maybery et al ., 2015; van Doesum et al ., 2008) and two were provided via DVD and/or the internet (Grove et al ., 2015b; van der Zanden et al ., 2010).…”
Section: Resultsmentioning
confidence: 99%
“…There was an extremely wide range of lengths and intensities of intervention from a 64‐minute DVD (Grove et al ., 2015b), to 50 visits a year (Brunette et al ., 2004), an 18‐month programme (Einbinder, 2010), to weekly family support for seven years (Dumaret et al ., 2009). However, most interventions involved between two and 18 sessions often delivered weekly.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[6162] Studies also highlight community and home-based interventions-including services that link families with environmental supports and provide access to financial resources and liaison and advocacy services. [636465]…”
Section: Interventions For Families Affected By Parental Mental Illnessmentioning
confidence: 99%
“…[61,62] Studies also highlight community and home-based interventions-including services that link families with environmental supports and provide access to financial resources and liaison and advocacy services. [63][64][65] A recent systematic review reported that preventive interventions with this population lead to significant improvement in parenting behaviors, [66] and a meta-analysis reported positive effects on the children's behavioral and emotional health, with interventions that jointly addressed parents and children yielding larger effects. [67] However, they also pointed out a lack of high-quality studies and recommended adoption of more rigorous research methods to test the interventions [66][67][68]…”
Section: Interventions For Families Affected By Parental Mental Illnessmentioning
confidence: 99%